2016
DOI: 10.1128/jcm.01159-16
|View full text |Cite
|
Sign up to set email alerts
|

The Brief Case: Neonatal Meningitis Caused by Listeria monocytogenes Diagnosed by Multiplex Molecular Panel

Abstract: c CASE On his 23rd day of life (DOL), a baby boy was transferred to our medical center from a community emergency department for treatment and management of presumed neonatal sepsis and meningitis.He was born full term via normal spontaneous vaginal delivery. His mother was primigravida with no medical complications during her pregnancy. Her prenatal lab results were negative for group B streptococci (GBS) at 36 weeks of gestation, and testing for HIV, syphilis, gonorrhea, chlamydia, and hepatitis B and C was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
10
5

Year Published

2016
2016
2025
2025

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 8 publications
4
10
5
Order By: Relevance
“…In addition, we could increase the amount of bacterial pathogens to 53% of the specimens, again this is more than in other published studies that observed positive ranges for bacterial pathogens between 15-37% [6,7,32,33]. Indeed, bacteria were the most abundant In concordance with other studies [6,7,[9][10][11][12][34][35][36][37][38], S. pneumoniae (17/30) In four samples, potentially false positive results of FilmArray ME panel occurred, including three samples tested positive for bacterial pathogens by multiplex PCR that remained culture negative.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In addition, we could increase the amount of bacterial pathogens to 53% of the specimens, again this is more than in other published studies that observed positive ranges for bacterial pathogens between 15-37% [6,7,32,33]. Indeed, bacteria were the most abundant In concordance with other studies [6,7,[9][10][11][12][34][35][36][37][38], S. pneumoniae (17/30) In four samples, potentially false positive results of FilmArray ME panel occurred, including three samples tested positive for bacterial pathogens by multiplex PCR that remained culture negative.…”
Section: Discussionsupporting
confidence: 88%
“…Using this selection criteria we selected 171/4623 CSF specimens for additional syndromic molecular testing. Overall we observed positive results in 56/171 (32%), which is higher than in other published studies [6,7,[9][10][11][12][34][35][36][37][38] and substantially higher compared to the multicenter evaluation study [6] and three other studies [7,32,33], that reported positivity rates of under 15% (p<0.0001). In addition, we could increase the amount of bacterial pathogens to 53% of the specimens, again this is more than in other published studies that observed positive ranges for bacterial pathogens between 15-37% [6,7,32,33].…”
Section: Discussioncontrasting
confidence: 65%
“…Patients who were positive for respiratory viruses were also less likely to be discharged with oral antimicrobial therapy (26). We previously described two cases in which rapid diagnosis of bacterial meningitis, attributable to Listeria monocytogenes and Haemophilus influenzae, with a molecular panel assay allowed definitive diagnosis and optimization of antimicrobial therapy (27)(28)(29). In this study, the availability of the HSV PCR results on a 24-h/7-day basis resulted in a significant reduction in the duration of acyclovir treatment in the postimplementation arm.…”
Section: Discussionmentioning
confidence: 80%
“…The diagnosis is challenging with convectional culture methods; PCR makes the isolation possible, as shown in previous case studies in neonates. 26,27 If not recognized and treated properly, L. monocytogenes can lead to meningitis and hydrocephalus, as complication 27 ; therefore, this bacteria should be considered in neonates with sepsis and meningitis. The second bacteria identified by conventional methods in a child aged above 12 months was S. pneumonia (n=1).…”
Section: Discussionmentioning
confidence: 99%